2010
DOI: 10.1111/j.1365-2141.2010.08214.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocerebrosidase deficiency dramatically impairs human bone marrow haematopoiesis in an in vitro model of Gaucher disease

Abstract: Summary One of the cardinal symptoms of type 1 Gaucher Disease (GD) is cytopenia, usually explained by bone marrow (BM) infiltration by Gaucher cells and hypersplenism. However, some cases of cytopenia in splenectomized or treated patients suggest possible other mechanisms. To evaluate intra‐cellular glucocerebrosidase (GlcC) activity in immature progenitors and to prove the conduritol B epoxide (CBE)‐induced inhibition of the enzyme, we used an adapted flow cytometric technique before assessing the direct eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 24 publications
0
35
1
1
Order By: Relevance
“…It requires the recruitment of progenitors from bone marrow (37). Most notably, biochemical inhibition of acid β-glucosidase in vitro impairs marrow hematopoiesis (38). Here, we show that the two accumulated GCase substrates, GL1 and Lyso-GL1, inhibit proliferation of HSC derived by GBA KO mice, although it seems that the progenitor population within bone marrow is unchanged in early stages of the disease.…”
Section: Discussionmentioning
confidence: 69%
“…It requires the recruitment of progenitors from bone marrow (37). Most notably, biochemical inhibition of acid β-glucosidase in vitro impairs marrow hematopoiesis (38). Here, we show that the two accumulated GCase substrates, GL1 and Lyso-GL1, inhibit proliferation of HSC derived by GBA KO mice, although it seems that the progenitor population within bone marrow is unchanged in early stages of the disease.…”
Section: Discussionmentioning
confidence: 69%
“…Nelly Reihani, 1 Jean-Benoit Arlet, 2 Michael Dussiot, 3 Thierry Billette de Villemeur, 4 Nadia Belmatoug, 5 Christian Rose, 6 Yves Colin-Aronovicz, 1 Olivier Hermine, 7 Caroline Le Van Kim 1* and Melanie Franco 1*…”
Section: Unexpected Macrophage-independent Dyserythropoiesis In Gauchunclassified
“…However, a growing number of studies performed on murine and in vitro models as well as those using cells from GD patients, indicate that the pathophysiology of GD may involve a wider array of cell types, including hematopoietic and mesenchymal cells, thymic T cells and progenitors, dendritic cells and osteoblasts. [5][6][7][8][9][10] We have previously shown that the red blood cells (RBCs) of GD patients exhibit abnormal morphological, rheological and functional properties, and could be considered additional factors in the GD pathophysiology on the basis that they can trigger ischemic events. 11 Importantly, a study of a large cohort revealed that anemia was the only risk factor for avascular osteonecrosis, the most debilitating skeletal complication for GD type 1 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cytopenias are secondary to hypersplenism, bone marrow infiltration by Gaucher cells and an intrinsic haemopoietic defect cells. 19 The increased bleeding tendency in patients with type 1 GD is related to thrombocytopenia, coagulation abnormalities, and defective platelet function. 20 The organomegaly can reach massive proportions and the splenomegaly is often the first presentation and the spleen is much more enlarged (median 15.2 times, up to 75 times) than the liver (up to 3 times).…”
Section: Clinical Presentationmentioning
confidence: 99%